Optimization of sowing time for adaptation to climate change and higher productivity of barley in the mid-Himalayas - Mahanta, Dibakar; Bisht, Jaideep Kumar; Kant, Lakshmi; Pattanayak, Arunava (Journal of Cereal Research, 2018)
Optimization of sowing date of barley was assessed by conducting three years’ experiment with different sowing dates and three popular varieties of barley in the mid-Himalayas. With the help of quadratic equation, it was estimated that maximum grain yield of barley could be achieved with sowing on 12th November, which provided 8% higher yield compared to the existing recommended sowing date of 25th October. The present recommendation will help to adapt the climatechange situation. Thousand-grain weight was the most important yield contributing attribute as found from the principal component analysis and correlation. Grain yield of barley could be modeled through the multi-linear regression equation with the help of yield attributes for the mid-Himalayas. The multi-linear regression equation will be highly useful for policymakers to estimate the yield of barley of either a district or a state in the mid-Himalayas. Doi.org/ 10.25174/2249-4065/2018/83644